Analysis of National Health Insurance Patient Satisfaction on Quality of Outpatient Services at Tugurejo Hospital Semarang - Desy Widyaningrum; Yohanes Budi Sarwo; Daniel Budi Wibowo (SOEPRA, 2021)
Abstract: Health service quality refers to the level of health service perfection in generating the patients’ satisfaction. In realizing qualified health services a hospital should have service standards to measure the service standard indicators. To measure whether the predetermined standards have been reached or not  indicators are used, namely to measure the compliance toward predetermined standards. Health service provision to JKN patients should be in accordance with the service standard so that the patients would feel satisfied. The incresing JKN membership coverage and the number of  JKN patients’ made the researcher interested to study.This study used a socio-legal approach having descriptive-analytical specification  that was conducted to the outpatient services provided by Tugurejo Regional Hospital Semarang. The type of data were primary and secondary data whereas the sampling technique was purposive sampling. The data gathering was conducted by literature and field studies. The data obtained were then quantitatively and qualitatively analyzed. The results of the study showed that the service standard of Tugurejo Regional Hospital was based on the the Central Java Governor's regulation by the issuance of the regulation of the Director of Tugurejo Regional Hospital Nr. 38 of 2017 on the Standard of the Tugurejo Regional Hospital of Central Java of 2018. In providing health services Tugurejo Regional Hospital should implement minimum service standard of Tugurejo Rgional Hospital Semarang that was in accordance with the Minister of Health of the Republic of Indonesia’s Decree  Nr. 129/Menkes/SK/II/2008 on Minimum Service Standards. The levels of JKN patients’ satisfaction in effectiveness dimension were feeling satisfied  44.4% and very satisfied 55.6%,. Based on efficiency dimension the level of satisfied was 60% and very satisfied was 40% whereas according to accessibility dimension the levels were dissatisfied at 11.1%, satisfied  46.7%, and very satisfied  42.2%. The acceptability/patient-centered dimension showed that 40% satisfied and 60% very satisfied whereas equitablity dimension showed 33.3% satisfied and 66.7% very satisfied. Safety dimension showed that 60% satisfied and 40% very satisfied. Some factors caused dissatisfaction, namely the facts that the health workers did not comply with the existing health service standards beside lack of patients’ awareness to their obligations.Keywords: service quality, hospital, satisfaction, JKN patient Abstrak: Mutu pelayanan kesehatan adalah yang merujuk pada tingkat kesempurnaan pelayanan kesehatan dalam menimbulkan rasa puas pada diri setiap pasien. Dalam mewujudkan pelayanan kesehatan  yang bermutu rumah sakit harus memiliki standar pelayanan untuk mengukur indikator standar pelayanan. Untuk mengukur tercapai atau tidaknya standar yang telah ditetapkan maka dipergunakan indikator, yaitu ukuran kepatuhan terhadap standar yang telah ditetapkan. Pada pelaksanaan dalam memberikan pelayanan kesehatan kepada pasien JKN harus diberikan sesuai dengan standar pelayanan sehingga pasien merasa puas. Cakupan kepesertaan JKN yang semakin meningkat dan  banyaknya kasus ketidakpuasan yang terjadi pada pasien pengguna JKN sehingga peneliti tertarik untuk meneliti.Penelitian ini menggunakan metode pendekatan yuridis sosiologis. Penelitian ini bersifat deskriptif analitis dilakukan pada pelayanan rawat jalan di RSUD Tugurejo Semarang. Jenis data menggunakan data primer dan data sekunder. Metode sampling yang digunakan yaitu purposive sampling. Metode pengumpulan data menggunakan studi pustaka dan studi lapangan. Teknik analisis data menggunakan analisis kuantitatif dan kualitatif.                             Hasil penelitian didapatkan RSUD Tugurejo Semarang memiliki standar pelayanan dibuat berdasarkan peraturan gubernur jawa tengah dengan dikeluarkannya Peraturan Direktur Rumah Sakit Umum Daerah Tugurejo Provinsi Jawa Tengah Nomor 38 Tahun 2017 Tentang Standar Rumah Sakit Umum Daerah Tugurejo Provinsi Jawa Tengah Tahun 2018 dalam memberikan pelayanan kesehatan RSUD Tugurejo Semarang menerapkan Standar Pelayanan Minimal Rumah Sakit Tugurejo Semarang sesuai dengan Keputusan Menteri Kesehatan Republik Indonesia Nomor 129/Menkes/SK/II/2008 tentang Standar Pelayanan Minimal. Tingkat kepuasan pasien JKN pada dimensi Effective pasien merasakan puas sebesar 44,4% dan sangat puas sebesar 55,6%, dimensi efficient didapatkan hasil responden puas 60% dan sangat puas 40%, dimensi Accessible didapatkan hasil tidak puas sebesar 11,1%, puas sebesar 46,7%, dan sangat puas sebesar 42,2%, dimensi Acceptable/patient-centred didapatkan hasil responden puas sebesar 40% dan sangat puas 60%, dimensi equitable didapatkan hasil responden puas sebesar 33,3% dan sangat puas sebesar 66,7%, pada dimensi safe didapatkan hasil responden puas sebesar 60% dan sangat puas sebesar 40%. Faktor yang menyebabkan ketidakpuasan dikarenakan tenaga kesehatan kurang mematuhi standar pelayanan kesehatan yang telah ditetapkan dan kurangnya kesadaran pasien akan kewajibannyaKata kunci: mutu pelayanan, rumah sakit, kepuasan, pasien JKN